Pengaruh Profitabilitas, Pertumbuhan Perusahaan, Struktur Modal dan Ukuran Perusahaan terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Sektor Infrastruktur yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Annisa Ridwan; Wahyumi Ekawanti (Jurnal Akuntan Publik, 2025)
This study aims to analyze the effect of profitability, firm growth, capital structure, and firm size on firm value in the infrastructure sector listed on the Indonesia Stock Exchange during the period 2020–2024. The data used in this study are secondary data obtained from company financial statements. The sampling technique employed was purposive sampling. The results show that profitability and firm size have a negative and significant effect on firm value. These findings indicate that increases in profitability and company scale do not automatically enhance market perceptions of firm value, possibly due to a misalignment between internal performance and investor expectations. Meanwhile, firm growth and capital structure do not have a significant effect on firm value. This suggests that the market does not yet regard growth or debt ratios as determining factors in evaluating companies in this sector. Furthermore, the results of this study highlight the importance of corporate management in managing internal factors that can influence market perceptions. Although profitability and company size negatively impact company value, this opens up opportunities for companies to focus more on communication strategies and information transparency with investors to mitigate investor expectations. Companies also need to revise their growth and capital structure policies to better align with market needs and the dynamics of the developing infrastructure sector. Furthermore, this study provides an important contribution to policymakers and financial practitioners in understanding the unique characteristics of the infrastructure sector in Indonesia. The insignificant influence of growth and capital structure suggests that external factors such as market conditions and regulations may be more dominant in determining company value in this sector. Therefore, further research could broaden its scope by incorporating macroeconomic variables or environmental and social aspects, which are currently of concern to investors in making investment decisions.